Effect of Plant Geometry on the Growth and Yield of Sugar Beet (Beta vulgaris L) cv. California-KWS: A Study on Inter-row and Intra-row Spacing - Imran Khan; Muhammad Iqbal; Malik Muhammad Hashim; Muhammad Munir; Atiq Ahmad; Abdul Aziz Khakwani (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
This study was aimed to assess the effect of plant geometry on the growth and yield of sugar beet under the agroclimatic conditions of D. I. Khan, Pakistan. Sugar beet, hybrid cv. California-KWS from Al-Moiz sugar mills (Dera Ismail Khan) was planted two seeds per hole on ridges at an inter-and intra-row spacing: 20 × 50, 20 × 60, 30 × 50, 30 × 60, 40 × 50, 40 × 60, 50 × 50 and 50 × 60 cm. The experiment was carried out in a Randomized Complete Block Design and replicated thrice. The parameters like plant height (cm), number of leaves, leaf area plant-1 (cm2), leaf and root weights per plant, root length and diameter (cm), TSS% (total soluble solids), sucrose (%), root and sugar yields (t ha-1) were studied. Results revealed that significantly maximum plant height, leaf area, leaf and root weights were observed in 40 × 50 cm spacing, number of leaves were maximum in 30 × 50 cm spacing, maximum root diameter was observed in 50 × 50 cm spacing while maximum root length, sucrose content, TSS, root and sugar yield were observed in 20 × 50 cm. Hence, the results showed that 20 × 50 cm is best spacing for obtaining highest yield and quality of sugar beet crop in the area.